Studies on the Biology of Tree Legumes - Rhizobium Symbiosis: Nodulation Pattern and Cross Inoculation Trials with the Tree Legumes and Cultivated Legumes - Basak, M K; Goyal, S K (Annals of Arid Zone, 2016)
-Â